(untitled) (Research, Society and Development, 2021)
Ivermectin, the pharmacological principle of a veterinary drug has an antiparasitic effect against endo and ectoparasites, it is widely used in veterinary practice. This drug is biotransformed in the liver, resulting in 3 metabolites, the most important being 24-hydroxy-methyl-dihydroavermectin B1. The liver is essential in regulating metabolism, in the synthesis of certain proteins, serving as a storage site for certain vitamins and iron, degrading certain hormones and inactivating and excreting certain drugs and toxins. Therefore, this study aimed to evaluate the morphology of the livers of pregnant rats treated with ivermectin. For this purpose, 30 albino rats were used, which were divided into 3 groups of 10 animals. The annimals were placed to mate and after the detection of pregnancy, the presence of sperm in the vaginal smear performed on the morning of the following day, being thus designated the first day of pregnancy, each animal was treated with ivermectin, in the dose corresponding to each group for 18 days, with administration every 3 (three) days, totaling 6 administrations. After this period, the liver was collected, weighed on an analytical balance and processed for light microscopy. The analysis of the relative weight of the livers of pregnant and non-pregnant rats did not reveal any significant difference between the experimental groups, where treatment with ivermectin at doses of 4.0 and 8.0 mg / kg did not alter the relative mass of the liver, nor did it show changes in color, texture, consistency and bleeding. Regarding the study through light microscopy, histopathological changes were not observed.